Evolving Consumer Trust in E-Commerce: How Consumers Make Sense of Their Experiences with Online Platforms - Shrestha, Debaki (My University, 2026)
Consumer trust is one of the most researched constructs in the studies related to ecommerce and previous research indicates that it impacts online purchase behaviour, satisfaction and platform use. While there has been prior research on the ante-cedents and consequences of trust, it has typically focused on consumer trust as an evaluative outcome that is influenced by platform characteristics. Less attention has been given to how consumers interpret trust relevant experiences and revise their trust judgements through repeated interactions with a platform. Although sense-making theory was applied to trust research in organizational or institutional set-tings, its application to consumer trust in the e-commerce seems limited. This thesis seeks to fill that void by using the perspective of sensemaking in relation to consum-er trust on e-commerce. The research question is focused on how consumers perceive their experiences with e-commerce platforms and how these perceptions affect their trust. The three dimensions of trustworthiness (ability, integrity, benevolence) are paired with Weick's seven properties of sensemaking to develop a framework for the understanding of trust as an interpretive process. The empirical study relies on nine semi-structured interviews with consumers in Finland who use Shein or Temu as their leading e-commerce platform and have a continuous experience of e-commerce with that platform of at least 12 months. Thematic analysis was used to analyse the data. The results indicate that consumer trust is developed through the active interpretation. The participants chose cues drawn from their experiences, which they filtered through their identities and their trust histories on platforms, assessed as to the three dimensions of trust, and determined whether these cues matched their current trust story. While most experiences were dealt with through routine sensemaking, accumulated cues that went beyond the current narrative led to sensemaking breakdown moments, which needed to be reinterpreted and recon-structed with respect to trust. This thesis provides a process-based explanation of consumer perceptions of trust and extends the sensemaking research into the con-text of the consumer e-commerce.
Keywords: trust; electronic commerce; consumer behaviour; consumers; interview study; customers; customer experience; fi=Taloustiede|en=Economics|; Master’s Programme in Strategic Business Development